ARTICLES ABOUT MUSICAL INSTRUMENTS IN SERBIA FROM THE 19TH AND EARLY 20TH CENTURIES IN THE WORKS OF TRAVEL WRITERS AND ETHNOGRAPHERS: THE BEGINNING OF THE THEMATIC AND METHODOLOGICAL PRINCIPLE OF SHAPING ETHNOORGANOLOGY (Heritage, 2026)
This paper presents ethnographic material, focusing on data documented by researchers from the 19th and first half of the 20th centurie regarding instrumental practice in Serbia. A comprehensive systematic review of the results, along with a comparative interpretation of the terminological, morphological, functional and sound characteristics of musical instruments, highlights the significant importance of the research of travel writers, ethnographers, ethnologists and geographers, within the contemporary ethnomusicological system framework. This comparative approach provides a basis for a more reliable consideration of the social role of certain sound props in the daily life of the individual and the community, with special reference to the importance that certain instruments have in a wider geographical area. The confirmed continuity of individual cultural phenomena justifies the formal legitimacy of the status of musical instrumental practices inscribed on the National List of Intangible Cultural Heritage of the Republic of Serbia. In addition to the assumption of authentic forms of orally transmitted musical folklore material, especially based on the perception of ideas for national liberation, this paper also sheds light on the relations between Eastern and Western influences observed in the set of musical instruments of this period. In parallel with mapping potential ethnic differentiations, articles on musical instruments also draw attention to the subjective experience evoked by situationally determined sound impulses. In an attempt to understand the perception of the effect, this approach is characteristic for works that suggest overcoming cultural differences. Pioneering attempts to point to interethnic socio-political encounters create the basis for the further development of scientific thought focused on the dynamism of social processes. Ethnographic identification of types and forms represent basis of the initial interest in musical instruments, which resonates with the inceptive development of ethnoorganology as a scientific discipline in general. The list of instruments is supplemented by selective documentation of non-musical indicators in whose constellation additional cultural analogies are observed. Despite heterogeneous structural and thematic concepts and methodological settings, the descriptive paradigm can be considered a relevant starting point for contemporary research endeavors. The ethnoorganographic approach is also a reference for the further development of ethnoorganology, which complements these tendencies with the analysis of musical aspects as key relations in the consideration of musical instruments.
Keywords: musical instruments, intangible cultural heritage, travelogue, ethnography, ethnoorganography, ethnoorganology.